2013
DOI: 10.1186/2192-1709-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in biological soil crust cover and composition

Abstract: Introduction: Communities change over time due to disturbances, variations in climate, and species invasions. Biological soil crust communities are important because they contribute to erosion control and nutrient cycling. Crust types may respond differently to changes in environmental conditions: single-celled organisms and bryophytes quickly recover after a disturbance, while lichens are slow growing and dominate favorable sites. Community change in crusts has seldom been assessed using repeated measures. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…However, coverage was higher for dry seasons compared to wet seasons. Changes in biocrust coverage support the idea that the communities in the biocrust are more dynamic during short time periods (45,46). Results found in our contribution are coincident with those reported by Belnap et al (2006), who observed a seasonal and yearly increase and decrease of the coverage of lichens and mosses when they evaluated the effect of temperature and precipitation on biocrust coverage.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, coverage was higher for dry seasons compared to wet seasons. Changes in biocrust coverage support the idea that the communities in the biocrust are more dynamic during short time periods (45,46). Results found in our contribution are coincident with those reported by Belnap et al (2006), who observed a seasonal and yearly increase and decrease of the coverage of lichens and mosses when they evaluated the effect of temperature and precipitation on biocrust coverage.…”
Section: Discussionmentioning
confidence: 52%
“…Despite the fact of the detected changes, the biocrust turned out to be stable. The difficulty in detecting changes in the community on short time scales may be because some taxa in biocrust have a small size, are cryptic and have slow growth rates (46). These changes reflect some differences in the growth rate of each organism and its response to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been observed by other investigators. However, others found a decline in species richness as well as in cover, often associated with altered community composition (Schulten 1985;Hilty et al 2004;Dettweiler-Robinso et al 2013), sometimes with a greater cover of short mosses, but a reduced cover of lichens and tall mosses. Fire impacts on biocrusts also extend to their functions.…”
Section: Firementioning
confidence: 96%
“…This was investigated by Weber et al (2013); Ecological characterization of soil-inhabiting and hypolithic soil crusts within the Knersvlakte, South Africa. Few longterm studies on biological crust communities are available, and so we present data on long-term changes in a biological crust community from the Columbia Basin, U.S.A., by Dettweiler-Robinson et al (2013); Long-term changes in biological soil crust cover and composition. Lastly, we present two studies that examine threats to biological soil crusts at the landscape scale.…”
mentioning
confidence: 99%